Ni(ii), Cu(ii) and Zn(ii) complexes with the 1-trifluoroethoxyl-2, 9, 10-trimethoxy-7-oxoaporphine ligand simultaneously target microtubules and mitochondria for cancer therapy. Issue 9 (12th March 2021) - Liao, Lan-Shan; Chen, Yin; Mo, Zu-Yu; Hou, Cheng; Su, Gui-Fa; Liang, Hong; Chen, Zhen-Feng
Abstract : Complexes 1–3 display potent anticancer activity against T-24 cell by disrupting mitochondria and microtubules. Furthermore, complex 1 exhibits almost same tumor growth inhibition activity in T-24 xenograft mouse model as cisplatin and paclitaxel. Abstract : Metal complexes of [NiL2 (NO3 )2 ] (1 ), [CuL2 (NO3 )2 ] (2 ) and [ZnL2 (NO3 )2 ] (3 ) with the 1-trifluoroethoxyl-2, 9, 10-trimethoxy-7-oxoaporphine (L ) ligand were synthesized. We discovered that complexes 1–3 exhibited considerable anticancer activity in vitro via simultaneously targeting microtubules and mitochondria. Complexes 1–3 impaired mitochondrial bioenergetic function by causing ATP depletion and mitochondrial membrane depolarization. They also triggered excessive generation of intracellular ROS and Ca 2+, activated caspase-3 and caspase-9, and triggered mitochondria-dependent apoptosis pathways. In addition, complexes 1–3 were shown by SPR and CETSA assays to have a good binding affinity for β-tubulin. Tubulin polymerization analysis suggested that complexes 1–3 promoted tubulin polymerization into microtubules, and disrupted the microtubule cytoskeleton network, which caused cell cycle arrest in the G2/M phase. Complexes 1–3 ultimately activated a strongly apoptotic response. Complexes 1 and 2 displayed high cancer growth inhibition efficacy in mice bearing T-24 xenografts, and had a good in vivo safety profile. Complexes 1–3 have the potential to become anticancer agents through targeting microtubule and mitochondria.